Analisis Dampak Program Merdeka Belajar–Kampus Merdeka (MBKM) terhadap Efektivitas Pembelajaran di Perguruan Tinggi - Said, Nur Muhammad; Rizal, Syaiful (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
The Merdeka Belajar-Kampus Merdeka (MBKM) program is an Indonesian educational initiative that gives students the opportunity to develop their skills. This program impacts the typical learning process at universities. This study discusses the MBKM program's impact on university learning processes. The study employs a qualitative research approach with a descriptive method. The data collection method used in this study is a literature review. The analysis employs triangulation of sources and data. The results indicate that the program positively impacts students by enhancing their hard and soft skills, which are aimed at addressing the challenges of the modern era. From a faculty perspective, the program requires innovation in classroom learning processes to align with contemporary needs. Additionally, this program increases the workload of lecturers, who are no longer solely focused on campus-based learning.